2017
DOI: 10.1002/jbm.b.33928
|View full text |Cite
|
Sign up to set email alerts
|

Human embryonic stem cell dispersion in electrospun PCL fiber scaffolds by coating with laminin‐521 and E‐cadherin‐Fc

Abstract: Advances in human pluripotent cell cultivation and differentiation protocols have led to production of stem cell-derived progenitors as a promising cell source for replacement therapy. Three-dimensional (3-D) culture is a better mimic of the natural niche for stem cells and is widely used for disease modeling. Here, we describe a nonaggregate culture system of human embryonic stem cells inside electrospun polycaprolactone (PCL) fiber scaffolds combined with defined extracellular proteins naturally occurring in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Microcarriers can be used in suspension bioreactor systems for PSC expansion [3638]. Using an electrospun polycaprolactone fiber system, Leino et al [36] expanded PSCs in a 3D environment. The authors observed a homogeneous culture environment and the cells maintained pluripotency.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Microcarriers can be used in suspension bioreactor systems for PSC expansion [3638]. Using an electrospun polycaprolactone fiber system, Leino et al [36] expanded PSCs in a 3D environment. The authors observed a homogeneous culture environment and the cells maintained pluripotency.…”
Section: Discussionmentioning
confidence: 99%
“…However, the cells failed to proliferate when low seeding density was used and could not be detached from the system without compromising cell viability due to the porosity of the fibers. Though these systems maintain the stemness of the cells, they exert the negative effect of bead agitation on cell yield, including increased risk of cell detachment [9, 32, 36]. However, lower agitation rates compromise nutrient exchange, resulting in larger aggregates that are difficult to dissociate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The contact angle is widely carried out to measure the fabricated materials hydrophilicity, since it implies the inclination of cell adhesion and proliferation of the material. PCL is inherently hydrophobic thus was usually modified with hydrophilic materials to improve its hydrophilicity, such as collagen, gelatin, laminin, and chitosan [33][34][35][36]. Herein, we found that the hydrophilicity of PCL was greatly increased after it was encapsulated within SF sheath.…”
Section: Properties Of the Pcl/sf Core-sheath Nfsmentioning
confidence: 99%
“…ECMbased scaffolds provide a biological matrix with environmental cues that can support the formation of proper vascular tissue. When the scaffold is coated with recombinant human laminin fibers, it supports the attachment and growth of naive stem cells in single-cell suspension [30]. A fibrin-coated pericardial ECM can be used as a material for cardiovascular surgery [31].…”
Section: Introductionmentioning
confidence: 99%